Sedimentary Processes, Environments and Basins 2007
DOI: 10.1002/9781444304411.ch13
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Comparing the Caledonian and Permo‐Triassic Erosion Surfaces with Present‐Day Topography Across Highland Scotland: Implications for Landscape Inheritance

Abstract: The Caledonian Orogeny marks a starting point for the evolution of the Scottish Highlands. There is debate as to the level of erosion that the Highlands have experienced since the Devonian and the extent to which the Highland landscape reflects Permo-Triassic rather than Caledonian events. Data on the position and elevation of the Caledonian and Permo-Triassic unconformities have been used to create topographic models of both surfaces. A variety of computer mapping packages have been used that allow the interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…The present-day high topography is better explained as the remnants of topography, which survived the extensional collapse, onshore and (mainly) offshore rifting processes following the Caledonian Orogeny, as well as erosion. A similar point of view has recently been expressed for the Scottish Caledonides (Macdonald et al, 2007). On this rifting background, the main contributions to the driving mechanism of our hypothesis are isostasy, climate, and erosion.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…The present-day high topography is better explained as the remnants of topography, which survived the extensional collapse, onshore and (mainly) offshore rifting processes following the Caledonian Orogeny, as well as erosion. A similar point of view has recently been expressed for the Scottish Caledonides (Macdonald et al, 2007). On this rifting background, the main contributions to the driving mechanism of our hypothesis are isostasy, climate, and erosion.…”
Section: Introductionmentioning
confidence: 62%
“…We instead consider the topography to be exhumed from topography produced during the Caledonian Orogeny, as for Scotland (Macdonald et al, 2007).…”
Section: The Ice Hypothesismentioning
confidence: 99%
“…Regarding the longevity of the Scottish Caledonides, which is doubted by Lidmar-Bergström and Bonow on the grounds of the paper by Macdonald et al (2007), which they believe we say the opposite of, which we do not, we have obtained the following personal comment (David Macdonald, 20 February 2009): "I believe that the Caledonian surface controls the present-day surface of the east Highlands and the eastern part of the Northern Highlands. I think that this block has been mostly above sea-level since the Devonian.…”
Section: Basins and Swells Hinge Lines And Cover Rocks Through Timementioning
confidence: 80%
“…They concluded that most of the erosion over the Scottish Highlands since formation of the Caledonian surface has been in cover rocks. Nielsen et al (2009) claim that the Macdonald et al (2007) paper provides support for their ICE hypothesis but, it shows that the basement was eroded to an Upper Devonian unconformity across the whole area, which has been repeatedly buried and re-exposed, which is against everything that Nielsen et al (2009) are claiming.…”
Section: Basins and Swells Hinge Lines And Cover Rocks Through Timementioning
confidence: 90%
“…In a paper on Scotland, Macdonald et al (2007) tried to reconstruct a sub-Silurian/Devonian surface (the Caledonian surface) and a Permo-Triassic surface. They concluded that most of the erosion over the Scottish Highlands since formation of the Caledonian surface has been in cover rocks.…”
Section: Basins and Swells Hinge Lines And Cover Rocks Through Timementioning
confidence: 99%